2012
DOI: 10.1167/iovs.11-8004
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Pupillography Identifies Ranibizumab-Induced Changes in Retinal Function for Exudative Age-Related Macular Degeneration

Abstract: Improvements in mfPOP contraction amplitudes and time to peak responses were measured in eyes treated with intravitreal ranibizumab; however, response delays appeared to be the most indicative of functional improvement. Confirmation of hypersensitivity in the extrafoveal field in a larger group may support this finding as a prognostic marker for good treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…In this study, the reference field for each protocol was computed as the median sensitivity at each visual field location measured across eyes and pupils (direct and consensual responses) of the normal controls. As in two previous studies, the ROC analysis also employed a form of crossvalidation, 16,18 the Leave-One-Out strategy. 26 In Leave-One-Out strategy, the ROC analysis for each normal subject's field is repeated with that field removed from the reference data, hence the data from a given normal subject's field do not bias its own classification.…”
Section: Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the reference field for each protocol was computed as the median sensitivity at each visual field location measured across eyes and pupils (direct and consensual responses) of the normal controls. As in two previous studies, the ROC analysis also employed a form of crossvalidation, 16,18 the Leave-One-Out strategy. 26 In Leave-One-Out strategy, the ROC analysis for each normal subject's field is repeated with that field removed from the reference data, hence the data from a given normal subject's field do not bias its own classification.…”
Section: Responsesmentioning
confidence: 99%
“…Those methods have been demonstrated to have diagnostic value in glaucoma, [14][15][16] early-stage diabetic retinopathy, 17 and age-related macular degeneration. [18][19][20] Aside from the 60 degree-wide stimuli used in most of those studies, mfPOP stimuli for the central retina have also been demonstrated. 18,20,21 Our original stimuli tested 24 regions/field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2009 our group has published several reports using multifocal pupillographic objective perimetry (mfPOP)123456789101112. The method was pioneered by others1314.…”
mentioning
confidence: 99%
“…The most successful mfPOP variant for retinal disease tests 44 regions of the macular field of each eye concurrently56912. The most powerful diagnostic measure for the earliest stages of AMD and diabetic eye disease is asymmetries in sensitivity between anatomically equivalent visual field regions of the two eyes256912. This is driven by a combination of visual field regions showing both sensitivity reductions and moderate sensitivity increases, and is assisted by the two eyes being tested simultaneously, providing a within subject control.…”
mentioning
confidence: 99%